2003
DOI: 10.1007/bf03035203
|View full text |Cite
|
Sign up to set email alerts
|

The actions and side effects of Anabolic Steroids in sport and social abuse

Abstract: Anabolic steroids (AS) derived from testosterone have both anabolic (muscle and strength enhancing) and a n d r o g e n i c (primary and s e c o n d a r y sexual) effects. Efforts to limit the androgenic while enhancing the anabolic effects have not been successful. Alterations to the structure of testosterone, so as to improve the pharmacokinetics of AS, have resulted in drugs, which are orally active, have a longer plasma half life and may be administered as depot injections. Therapeutic doses of AS produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…While some side effects are mild, such as stomach upset and heartburn associated with bisphosphonate pills, some are more concerning, such as blood clots, stroke, and certain types of cancers associated with the SERMs [ 10 ]. In addition, anabolic steroids that are used in treating BDs are also linked to adverse effects which, in addition to those already mentioned for other drugs, include toxicity to vital organs such as the brain, liver, kidney, and reproductive organs, and impairment of cognitive and cardiovascular functions and several other systemic alterations [ 13 , 14 ]. Thus, the need arises for alternative treatments with little or no health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…While some side effects are mild, such as stomach upset and heartburn associated with bisphosphonate pills, some are more concerning, such as blood clots, stroke, and certain types of cancers associated with the SERMs [ 10 ]. In addition, anabolic steroids that are used in treating BDs are also linked to adverse effects which, in addition to those already mentioned for other drugs, include toxicity to vital organs such as the brain, liver, kidney, and reproductive organs, and impairment of cognitive and cardiovascular functions and several other systemic alterations [ 13 , 14 ]. Thus, the need arises for alternative treatments with little or no health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…1 The anabolic activity of testosterone and its synthetic derivatives results in significant muscle mass and strength gains, 2 due to increased nitrogen retention and protein synthesis in skeletal muscle cells and diminished catabolism. [3][4][5] AAS were initially developed for therapeutic purposes, but today, the greatest prevalence of AAS use is among athletes who seek improvements in their performance in sports practice and among individuals doing recreational muscle building, who are motivated by constructing a body image that satisfies them. 6,7,8 Epidemiological evidence has indicated that there is high prevalence of illicit use of these drugs in the United States, 9 Australia, 10 United Kingdom, Greece, Bulgaria and Croatia.…”
Section: Introductionmentioning
confidence: 99%
“…1 The anabolic activity of testosterone and its synthetic derivatives results in significant muscle mass and strength gains, 2 due to increased nitrogen retention and protein synthesis in skeletal muscle cells and diminished catabolism. 3 5…”
Section: Introductionmentioning
confidence: 99%